1996
DOI: 10.1007/bf00199513
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic structure of glomerular capillary loop as revealed by an in vivo cryotechnique

Abstract: Morphological studies using immersion or perfusion fixation methods do not reveal the ultrastructure of functioning kidneys with normal circulation. A simple apparatus was developed for freezing the kidneys in vivo without stopping the blood supply, and the ultrastructure of the glomerular capillary loops was examined under different haemodynamic conditions. Mouse kidneys were frozen under normal blood flow conditions; others were frozen in the same way after ligation of the abdominal aorta at a point caudal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 28 publications
2
84
0
Order By: Relevance
“…In the seminiferous tubules, as 4.1G was relatively immunolocalized as round and/or arch-shaped patterns in the basal compartment as well as honeycomb patterns in the adluminal compartment . In this study, we further evaluated the 4.1G immunolocalization at various stages of the mouse seminiferous cycle with 'in vivo cryotechnique (IVCT)' (Ohno et al 1996) and found different 4.1G distributions among the various stages. In addition, with immunoelectron microscopy, 4.1G was found to be immunolocalized not only in Sertoli cells, but also in a subset of germ cells including spermatogonium.…”
Section: Introductionmentioning
confidence: 99%
“…In the seminiferous tubules, as 4.1G was relatively immunolocalized as round and/or arch-shaped patterns in the basal compartment as well as honeycomb patterns in the adluminal compartment . In this study, we further evaluated the 4.1G immunolocalization at various stages of the mouse seminiferous cycle with 'in vivo cryotechnique (IVCT)' (Ohno et al 1996) and found different 4.1G distributions among the various stages. In addition, with immunoelectron microscopy, 4.1G was found to be immunolocalized not only in Sertoli cells, but also in a subset of germ cells including spermatogonium.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo cryotechnique is a new and original method which can prevent morphological and immunohistochemical alterations caused by stopping of blood circulation that induces anoxia and rapid loss of blood volume and pressure [17,18,36]. Such a method can, therefore, be expected to enable more detailed immunohistochemical analyses of transient and dynamic morphology in living animal organs.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of blood supply into some organs can easily modify their ultrastructure and molecular distributions, presumably induced by anoxia and rapid loss of blood volume and pressure [17,18,26,27,[30][31][32]35]. In addition, such loss of blood supply, inevitable in experimental studies involving conventional chemical fixation or common QF of fresh tissue specimens, sometimes modifies the immunoreactivity of various functional molecules, due to the rapid ischemia, which induces diverse responses in living animal organs [8,29].…”
Section: Significance Of Cryotechniques For Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in the past decade, the in vivo cryotechnique has been developed to achieve better detection of in vivo morphology [4], using a combination of cooled metal cryoknife with isopentane-propane liquid cryogen. After in vivo freezing, followed by freeze-substitution or freeze-fracture replica method, the frozen specimens can be processed for light or electron microscopic observation, as shown in Figure 2.…”
Section: Introductionmentioning
confidence: 99%